Effect of vitamin D intake on quality of life parameters in office workers - A. T. Sharman; Sh. K. Adambekov; A. A. Imandosova; G. F. Elemesova (Фармакоэкономика)
Objective: to study the prevalence of vitamin D deficiency and analyze the results of therapy in office workers, including an assessment of the quality of life.Material and methods. An observational non-interventional cross-sectional, cohort, prospective phase IV clinical study included office workers (151 people, age 18–44 years), who were prescribed an aqueous solution of vitamin D. The concentration of 25(OH)D in the blood of patients was measured before and after undergoing treatment. The duration of therapy, depending on the degree of deficiency, was 4 or 8 weeks. The SF-36 scale was used to assess the physiological and psychological status.Results. In 75.5% of the study participants, a insufficiency or deficiency of vitamin D was detected. Differences in the average content of 25(OH)D in blood serum before and after treatment with vitamin D were statistically significant. The level of vitamin D in blood serum, measured by the content of its metabolite 25(OH)D <30 ng/ml, is regarded as suboptimal, i.e. its insufficiency occurs, and <20 ng/ml – as vitamin D deficiency (p<0.0001). The SF-36 score showed significant statistically significant improvements in overall health, physical functioning, and pain in individuals with vitamin D deficiency after vitamin D supplementation. The use of multiple linear regression demonstrated an association of serum 25(OH)D levels with vitamin D-rich foods taken less than once a week.Conclusions. Vitamin D deficiency is very common among office workers: 75.5% had D 25(OH)D levels below 30 ng/ml. Vitamin D deficiency is corrected by taking this vitamin. Vitamin D supplementation helps to improve physical and mental health indicators. Serum 25(ОН)D levels are associated with intake of vitamin D-rich foods and duration of vitamin D treatment.